Endothelial activation and fibrotic changes are impeded by laminar flow-induced CHK1-SENP2 activity through mechanisms distinct from endothelial-to-mesenchymal cell transition - Minh T. H. Nguyen; Minh T. H. Nguyen; Masaki Imanishi; Shengyu Li; Khanh Chau; Priyanka Banerjee; Loka reddy Velatooru; Kyung Ae Ko; Venkata S. K. Samanthapudi; Young J. Gi; Ling-Ling Lee; Rei J. Abe; et al. (Frontiers in Cardiovascular Medicine, 2023)
BackgroundThe deSUMOylase sentrin-specific isopeptidase 2 (SENP2) plays a crucial role in atheroprotection. However, the phosphorylation of SENP2 at T368 under disturbed flow (D-flow) conditions hinders its nuclear function and promotes endothelial cell (EC) activation. SUMOylation has been implicated in D-flow-induced endothelial-to-mesenchymal transition (endoMT), but the precise role of SENP2 in counteracting this process remains unclear.MethodWe developed a phospho-specific SENP2 S344 antibody and generated knock-in (KI) mice with a phospho-site mutation of SENP2 S344A using CRISPR/Cas9 technology. We then investigated the effects of SENP2 S344 phosphorylation under two distinct flow patterns and during hypercholesteremia (HC)-mediated EC activation.ResultOur findings demonstrate that laminar flow (L-flow) induces phosphorylation of SENP2 at S344 through the activation of checkpoint kinase 1 (CHK1), leading to the inhibition of ERK5 and p53 SUMOylation and subsequent suppression of EC activation. We observed a significant increase in lipid-laden lesions in both the aortic arch (under D-flow) and descending aorta (under L-flow) of female hypercholesterolemic SENP2 S344A KI mice. In male hypercholesterolemic SENP2 S344A KI mice, larger lipid-laden lesions were only observed in the aortic arch area, suggesting a weaker HC-mediated atherogenesis in male mice compared to females. Ionizing radiation (IR) reduced CHK1 expression and SENP2 S344 phosphorylation, attenuating the pro-atherosclerotic effects observed in female SENP2 S344A KI mice after bone marrow transplantation (BMT), particularly in L-flow areas. The phospho-site mutation SENP2 S344A upregulates processes associated with EC activation, including inflammation, migration, and proliferation. Additionally, fibrotic changes and up-regulated expression of EC marker genes were observed. Apoptosis was augmented in ECs derived from the lungs of SENP2 S344A KI mice, primarily through the inhibition of ERK5-mediated expression of DNA damage-induced apoptosis suppressor (DDIAS).SummaryIn this study, we have revealed a novel mechanism underlying the suppressive effects of L-flow on EC inflammation, migration, proliferation, apoptosis, and fibrotic changes through promoting CHK1-induced SENP2 S344 phosphorylation. The phospho-site mutation SENP2 S344A responds to L-flow through a distinct mechanism, which involves the upregulation of both mesenchymal and EC marker genes.